Correlation between Cellular Autophagy and Color Changes in Qinchuan Cattle Meat during Postmortem Aging - LIANG Yanqun, SI Jianfang, MA Meng, GAO Shuang, LI Yalei, LUO Ruiming (Shipin Kexue)
In order to investigate the occurrence of cellular autophagy and its effect on the meat color of Qinchuan cattle during postmortem aging, the changes in the meat color, relative myoglobin content, metmyoglobin reductase activity (MRA), beclin1, microtubule-associated protein light chain 3-II (LC3-II), autophagy-related protein 7 (ATG7), sequestosome 1 (p62), caspase 8, mitochondrial membrane potential (MMP), reactive oxygen species (ROS) levels of the longissimus dorsi muscle of Qinchuan cattle were determined at different time points during postmortem aging at 4 ℃. It was found that as the aging time was prolonged, L* and a* values as well as beclin1, LC3-II and ATG7 protein expressions initially increased and subsequently decreased, caspase 8, p62 and ROS showed an opposite trend; the relative contents of deoxymyoglobin (DeoMb) and oxymyoglobin (OxyMb), MMP and MRA decreased, whereas b* value and the relative content of metmyoglobin (MetMb) increased. Moreover, the key proteins related to cellular autophagy were expressed to different degrees during the postmortem process, and muscle cells exhibited autophagy, the strongest autophagic activity being observed at 96 h. Correlation analyses showed a highly significant correlation among the key proteins related to cellular autophagy (P < 0.01), indicating that these proteins were closely related to each other in cellular activity. There were significant correlations between meat color parameters and cellular autophagy-related proteins and mitochondrial function at 0-96 h during the postmortem process (P < 0.05). The above results showed that the changes in mitochondrial function and autophagy in myoblasts during the early postmortem period affect meat color, and beclin1, LC3-II, ATG7, p62, and caspase 8 can be used as biomarkers to predict the changes of meat color during the postmortem process.